2015
DOI: 10.1002/2015gl065959
|View full text |Cite
|
Sign up to set email alerts
|

Slow Cenozoic uplift of the western Andean Cordillera indicated by cosmogenic 3 He in alluvial boulders from the Pacific Planation Surface

Abstract: To determine the mechanisms responsible for mountain belt growth, it is important to accurately establish the timing of surface uplift. Here we exploit the altitude control on the production rate of in situ cosmogenic nuclides to test the hypothesis that the Andes was uplifted in the late Miocene. High concentrations of in situ cosmogenic 3He (3Hecos) have previously been measured in alluvial boulders on the western flank of the Central Andes, northern Chile (Evenstar et al. 2009). These are consistent with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 53 publications
2
29
0
1
Order By: Relevance
“…This is consistent with the findings of Evenstar et al . [] based on the concentration of cosmogenic 3 He in alluvial boulders located in the piedmont, that most of the current elevation in the area was achieved before 13.4 Ma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with the findings of Evenstar et al . [] based on the concentration of cosmogenic 3 He in alluvial boulders located in the piedmont, that most of the current elevation in the area was achieved before 13.4 Ma.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Evenstar et al . [] quantified uplift by using cosmogenic nuclide data for two sites at which some of our samples are co‐located. They showed that all but a small fraction of the current site elevations (1690 m and 1900 m) must have existed at the end of the Middle Miocene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of the Andean cordillera that extends from northern Venezuela to southern Chile has been proposed as the main driver of diversification in the Neotropical region (Hoorn et al., ). However, the timing and magnitude of surface uplift along the Andean cordilleras is highly controversial (see, e.g., Evenstar, Stuart, Hartley, & Tattitch, and references therein). Despite such uncertainty, it is undeniable that the formation of the Andes provided new ecological conditions along the slopes of the cordillera, modified the climate of the Neotropical region and deeply affected the formation of the Amazonian basin by depositing large quantities of sediment and modifying water drainage patterns (Hoorn et al., ).…”
Section: Introductionmentioning
confidence: 99%